Mapping the Distribution of High Buildings in West Medan Subdistrict Using Geographic Information System (GIS) - Citra Utami; Dina Septiningtyas; Lisherly R Debataraja; Tetra Oktaviani; Fahrizal Zulkarnain (LPPM Politeknik Aceh Selatan, 2024)
Cities are one of the main centers for the development of urban areas. The opportunity for investment activities in a city is one of the biggest pull factors for migration. Medan's rapid development can be seen from the construction of many tall buildings such as malls, apartments, and offices. The granting of permits for the construction of these high-rise buildings is closely related to urban spatial planning. Medan City does not yet have a 3D map of the distribution of high-rise buildings, there is only data on the number and location of high-rise buildings. Therefore, urban spatial mapping of high-rise buildings is needed. The model in this research uses a GIS computer model integrated in Arcgis software by taking the object of West Medan sub-district. The results of this study are the suitability of the distribution of tall buildings with a fairly dense uniform pattern in the West Medan sub-district where this sub-district is indeed a service center for trade/business, services and provincial and municipal government activities, and the economy